The Leaky Pipeline of Women in Plastic Surgery: Embracing Diversity to Close the Gender Disparity Gap. (30th October 2019) - Moak, Teri N; Cress, Phaedra E; Tenenbaum, Marissa; Casas, Laurie A
Abstract: The Balance for Better campaign theme of the 2019 International Women's Day prompted a closer look at diversity within the plastic surgery specialty. Gender balance in the United States has improved through many organizational efforts and enactment of laws. Unfortunately, despite these endeavors, statistics show that men still enjoy greater financial and career success. Within the field of medicine, a similar trend has been observed. Although women constitute 50% of medical school graduates, the majority still enter fields outside of surgical subspecialties. In comparison to other surgical subspecialties, women are most represented in plastic surgery. Unfortunately, significant gender discrepancies remain in postgraduate practice including academic practice rank, societal board membership, invited speaker opportunities, and compensation, to name a few. The "leaky pipeline" of women describes the precipitous decline in the numbers of women at each step up the professional ladder. We explore the multifaceted nature of this phenomenon and highlight factors that contribute to limiting female growth within the plastic surgery profession. We also emphasize the continued growth of female plastic surgeon presence in all sectors despite these existing obstacles. We submit that continued leadership, mentorship, and sponsorship provided by both male and female physicians in the field will facilitate future leadership, advance gender parity, and cultivate a sense of belonging within the plastic surgery community, allowing brilliant minds to flourish and the profession to thrive.